Autoimmune bullous dermatoses in cancer patients treated by immunotherapy: a literature review and Italian multicentric experience - Merli, Martina; Accorinti, Martina; Romagnuolo, Maurizio; Marzano, Angelo; Di Zenzo, Giovanni; Moro, Francesco; Antiga, Emiliano; Maglie, Roberto; Cozzani, Emanuele; Parodi, Aurora; Gasparini, Giulia; Sollena, Pietro; et al. (Frontiers in Medicine, 2023)
Cutaneous immune-related adverse events are frequently associated with immune checkpoint inhibitors (ICIs) administration in cancer patients. In fact, these monoclonal antibodies bind the cytotoxic T-lymphocyte antigen-4 and programmed cell death-1/ligand 1 leading to a non-specific activation of the immune system against both tumoral cells and self-antigens. The skin is the most frequently affected organ system appearing involved especially by inflammatory manifestations such as maculopapular, lichenoid, psoriatic, and eczematous eruptions. Although less common, ICI-induced autoimmune blistering diseases have also been reported, with an estimated overall incidence of less than 5%. Bullous pemphigoid-like eruption is the predominant phenotype, while lichen planus pemphigoides, pemphigus vulgaris, and mucous membrane pemphigoid have been described anecdotally. Overall, they have a wide range of clinical presentations and often overlap with each other leading to a delayed diagnosis. Achieving adequate control of skin toxicity in these cases often requires immunosuppressive systemic therapies and/or interruption of ICI treatment, presenting a therapeutic challenge in the context of cancer management. In this study, we present a case series from Italy based on a multicenter, retrospective, observational study, which included 45 patients treated with ICIs who developed ICI-induced bullous pemphigoid. In addition, we performed a comprehensive review to identify the cases reported in the literature on ICI-induced autoimmune bullous diseases. Several theories seeking their underlying pathogenesis have been reported and this work aims to better understand what is known so far on this issue.